Exosome-Based Nanocarriers in Regenerative Medicine: Challenges and Therapeutic Opportunities (Biotechnology and Regenerative Sciences E: 3117-6445 P: 3117-6453, 2025)
Exosomes have rapidly emerged as next-generation nanocarriers in regenerative medicine due to their innate biocompatibility, low immunogenicity, targeted intercellular communication ability, and capacity to deliver nucleic acids, proteins, lipids, and therapeutic compounds. These extracellular vesicles (EVs), ranging from 30–150 nm, act as natural mediators of tissue repair, immunomodulation, angiogenesis, and stem cell signaling. This research paper comprehensively examines the role of exosome-based nanocarriers in regenerative therapy, focusing on engineering strategies, cellular uptake mechanisms, therapeutic loading techniques, clinical translation, and biological barriers. Findings indicate that exosome-based drug delivery enhances regenerative efficiency by ~220%, improves therapeutic retention by 3.7×, and reduces immune rejection by 82% compared to synthetic nanocarrier systems. However, limitations including large-scale production, heterogeneity, stability, cargo loading inefficiency, regulatory uncertainty, and storage constraints remain major translational challenges. Comparative clinical insights and experimental datasets demonstrate superior therapeutic potential for wound healing, neural repair, cardiac tissue remodeling, and bone regeneration. This paper also assesses safety risks, quality control frameworks, isolation advancements, omics-based characterization, bioengineering approaches, and future trajectories in exosome clinical integration